ENHANCING CUSTOMERS’ LOYALTY THROUGH SERVICE QUALITY - Santoso, Raymond; Devi Rachmasari; Claudius Bona (Politeknik Ubaya, 2025)
This study explores how the delivery of desirable services influences the overall performance of a service company in Kediri, particularly focusing on customer satisfaction, loyalty, and business outcomes. In the modern service industry, companies are expected to deliver fast, responsive, and personalized services to retain customers and remain competitive. A service company, a service-oriented enterprise, has been experiencing challenges in meeting these rising expectations. The writer used a descriptive qualitative approach using a case study approach consisting of observation, questionnaires, and interviews with customers, employees, and the business owner. This research investigates service delivery issues and their impact on customer experience and business performance. The findings reveal that the main problems are slow service response, lack of employee training, and low empathy in customer interactions. To address these issues, the company manages a feedback system, improves standard operating procedures (SOPs), holds regular service training, and implements better staffing strategies. These improvements yield 30% customers increase, 72% customers are satisfied, 18% neutral and 10% dissatisfied.